Theory, practice and techniques in project management. (3G E-Learning, 2018)
“Theory, Practice and Techniques in Project Management” explains the principles and theories of project management and describes how and when the different project management techniques can be applied. The role of different project management techniques to implement projects successfully has been widely established in areas such as the planning and control of time, cost and quality. In spite of this the distinction between the project and project management is less than precise. This book aims to identify the overlap between the definition of the project and project management and to discuss how the confusion between the two may affect their relationship. It identifies the different individuals involved on the project and project management, together with their objectives, expectations and influences. It also discusses the implications of the situation where the project fails but the project management process is perceived to have succeeded or vice versa. The purpose of this book is to provide some understanding and guidelines on the way medium sized and large Projects in a global environment can be initiated and managed.